Ergosterol is mainly located in the cytoplasmic leaflet of the yeast plasma membrane. (26th February 2018) - Solanko, Lukasz M.; Sullivan, David P.; Sere, Yves Y.; Szomek, Maria; Lunding, Anita; Solanko, Katarzyna A.; Pizovic, Azra; Stanchev, Lyubomir D.; Pomorski, Thomas Günther; Menon, Anant K.; Wüstner, Daniel
Abstract : Transbilayer lipid asymmetry is a fundamental characteristic of the eukaryotic cell plasma membrane (PM). While PM phospholipid asymmetry is well documented, the transbilayer distribution of PM sterols such as mammalian cholesterol and yeast ergosterol is not reliably known. We now report that sterols are asymmetrically distributed across the yeast PM, with the majority (~80%) located in the cytoplasmic leaflet. By exploiting the sterol‐auxotrophic hem1 Δ yeast strain we obtained cells in which endogenous ergosterol was quantitatively replaced with dehydroergosterol (DHE), a closely related fluorescent sterol that functionally and accurately substitutes for ergosterol in vivo . Using fluorescence spectrophotometry and microscopy we found that <20% of DHE fluorescence was quenched when the DHE‐containing cells were exposed to membrane‐impermeant collisional quenchers (spin‐labeled phosphatidylcholine and trinitrobenzene sulfonic acid). Efficient quenching was seen only after the cells were disrupted by glass‐bead lysis or repeated freeze‐thaw to allow quenchers access to the cell interior. The extent of quenching was unaffected by treatments that deplete cellular ATP levels, collapse the PM electrochemical gradient or affect the actin cytoskeleton. However, alterations in PM phospholipid asymmetry in cells lacking phospholipid flippases resulted in a more symmetric transbilayer distribution of sterol. Similarly, an increase in the quenchable pool of DHE was observed when PM sphingolipid levels were reduced by treating cells with myriocin. We deduce that sterols comprise up to ~45% of all inner leaflet lipids in the PM, a result that necessitates revision of current models of the architecture of the PM lipid bilayer. Abstract : The transbilayer distribution of sterols in the plasma membrane (PM) is highly debated. Exploiting yeast cells in which ergosterol is entirely replaced with closely related fluorescent dehydroergosterol (DHE), we show that PM sterols reside primarily (~80%) in the inner leaflet of the yeast PM. Maintenance of this pronounced asymmetry does not require metabolic energy but is weakened upon sphingolipid depletion and loss of PM phospholipid asymmetry.